Beta-Carotene, Anthocyanin, Antioxidant Activity, and Microbiological Quality of Steamed Sponge Cakes for Alternative Post-Disaster Snack Food - Rahman, Nurdin; Ariani, Ariani; Rakhman, Aulia (Journal of Health and Nutrition Research, 2025)
The research aims to analyze the levels of beta carotene, anthocyanin, antioxidant power (IC50), and yeast numbers of steamed sponge cake mold based on a combination of purple sweet potato flour (Ipomoea Batatas L.) and orange sweet potato flour (Ipomoea Batatas L.) as an alternative post-disaster snack. The type of research was a Factorial Completely Randomized Design (CRD) using a ratio of wheat flour and a combination of purple sweet potato flour and orange sweet potato flour, namely 100:0 (F0), 80:20 (F1), 70:30 (F2), 60: 40 (F3), and 50:50 (F4). Data analysis included beta carotene, anthocyanin, IC50 of antioxidant activity, and mold yeast numbers. The steamed sponge cake with the highest anthocyanin content is formula F4 (2.64 mg/100 g), followed by formula F3 (1.57 mg/100 g). The β-carotene levels (mg/100g) show that the F3 formula is the highest, at 38.83 mg/100 g, and the F2 formula is 29.33 mg/100 g. The most potent antioxidant power is the F4 formula of 91.84 µg/mL. Formula F4, at a dilution of 10-6, obtained the lowest yeast number, 7 CFU/mL. Formula F4 is the best formula of the four formulas tested. Formula F4 has high levels of anthocyanin, β-carotene, antioxidant power, and the lowest number of yeast molds.